2019
DOI: 10.12968/bjmh.2018.0030
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in illness among people with mental ill health: a nursing perspective

Abstract: Background/Aims: Uncertainty in illness is a well-known concept in health care literature. A considerable volume of research has investigated how people adapt to different health conditions and how the concept of uncertainty in illness relates to those populations. The aim of this article is to explore the concept of uncertainty in illness among mental health nurses and to provide an understanding of its relevance to people living with mental ill health. Method: A focus group was conducted with mental health n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…According to Mishel, individuals may be occupied with uncertainty, ambiguity or confusion regarding their illness (symptoms, cause, course or treatment). Those uncertainties are the main variables among individuals with schizophrenia (Baier, 1995; Wolfensberger et al , 2019; Taş Bora and Buldukoğlu, 2020). Our study revealed a wide range of perspectives on uncertainty in illness among individuals with schizophrenia living in the community in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Mishel, individuals may be occupied with uncertainty, ambiguity or confusion regarding their illness (symptoms, cause, course or treatment). Those uncertainties are the main variables among individuals with schizophrenia (Baier, 1995; Wolfensberger et al , 2019; Taş Bora and Buldukoğlu, 2020). Our study revealed a wide range of perspectives on uncertainty in illness among individuals with schizophrenia living in the community in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors affect the long recovery process in individuals with schizophrenia, including the duration of illness, the severity of symptoms, stigma, discrimination, poor compliance with antipsychotic medication, relapse, lack of social support, lack of understanding of the illness, cognition impairment, substance use disorders, medication effects, unemployment and low family economic status (Tsang and Chen, 2007;Tan et al, 2014;Zipursky, 2014;Padgett et al, 2016;Nowak et al, 2017;Vita and Barlati, 2018;Singla et al, 2020). On the other hand, several other recent studies revealed positive outcomes of schizophrenia treatment, especially those with adequate social support, perceived higher levels of emotional support and perceived higher satisfactory levels of recovery (Buonocore et al, 2018;Wolfensberger et al, 2019;El-monshed and Amr, 2020). Thus, it could be concluded that schizophrenia can be cured, even if it takes a long time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study investigating the concept of uncertainty in illness among mental health nurses, nurses suggested that recognizing uncertainty and supporting service users in coping with it could be a precious intervention that mental health nurses can provide. However, mental health professionals need to be more aware of the “uncertainty in illness” concept (Wolfensberger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%